Peran Investasi Dalam Negeri Dan Investasi Asing Terhadap Perekonomian Provinsi-Provinsi Di Pulau Sumatera - Jorgi Aprilio Sinambela; Heru Wahyudi; Ukhti Ciptawaty (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Economic growth is inseparable from investment coming in, both PMDN and FDI, because with the increasing number it means that it can be used as capital so that the inflow of investment will spur the stock of the workforce in helping economic activity. This study will examine the effect of investment and the workforce on the development of economic growth in 10 provinces on the island of Sumatra. This research is in the form of a quantitative descriptive study using secondary data and in the form of Panel Data, time series used in the 2011-2021 period, with regional observations or (cross sections) of 10 Provinces, The method used is Multiple Linear Regression Analysis (OLS). . The results of the research show that the results of Domestic Investment (PMDN) and Foreign Investment (PMA) have a positive and significant influence on the Economic Growth of 10 Provinces on Sumatra Island in 2011-2021.